Patch exploitation behaviour by a parasitoid of a forest pest: The influence of host cues and intra- and interspecific interactions - Suans Giorgi, Melisa Andrea; Fischbein, Deborah; Corley, Juan Carlos (Wiley, 2024)
For parasitoids, host foraging is the most significant activity for their reproductive success, as it directly translates into offspring production. Therefore, foraging behaviour and patch-use decisions by parasitoids still attract research interest, especially when the studied species are biological control agents. In laboratory conditions, we studied the patch exploitation behaviour of Megarhyssa nortoni (Hymenoptera: Ichneumonidae), a larval–pupal parasitoid of several woodwasps (Hymenoptera: Siricidae), exposed to intra- and interspecific interactions. It is known that M. nortoni females are attracted to the symbiotic fungus carried by its hosts, which support host larval development inside the wood. Additionally, in the introduced range where the species has been released in biocontrol programs aimed at managing invasive Sirex noctilio populations, Megarhyssa nortoni coexists with the egg–larval parasitoid Ibalia leucospoides. First, we investigated whether host–fungal symbiont cues and direct presence of conspecific females affected patch time allocation and oviposition behaviour of M. nortoni, as both stimuli could provide information on concealed hosts. Second, we studied the influence of prior parasitism by I. leucospoides on patch time allocation decisions and oviposition behaviour. The main results showed that females modulated their responses to the fungal cues when foraging simultaneously with conspecifics. Also, patch-leaving tendencies and patch residence times were not affected when females foraged patches previously exploited by I. leucospoides; indeed, they probed these patches more frequently. Our study contributes to the understanding of patch-use decisions made by parasitoids and their impact on the biological control of damaging insect populations, particularly in a context of two parasitoid species and one host.